La gastronomía típica en el desarrollo turístico del cantón Vinces. - Lara Velasco, Jhoselyn Isabel (2016)
In the current research project has been carried out an analysis of the typical cuisine, their essential contribution and fundamental to the development of tourism and thus try to enhance and recover the nutritional importance that gives us each of these dishes in Canton Vinces Los Rios province. Today there is no economic, educational and formal incentive by the, tourism professionals sectional authorities to improve the quality of presentation and innovation and customer service, which would generate more tourists and people living in the same Canton, benefiting the general population, creating more jobs places such farmers and fishermen who sell their own products in the area who are responsible for the development and preparation of the ancestral food . Moreover verify the acceptance of gastronomic tourism in those who before traveling not only think distracted or meet an attractive place but choose to taste the cuisine and if this is typical much better because it represents the history, culture, traditions and ancestral knowledge with which account Vinces Canton thus achieve their meals spread nationally and internationally.